Site-Specific Neuromodulation of Detrusor and External Urethral Sphincter by Epidural Spinal Cord Stimulation - Sysoev, Yuriy; Bazhenova, Elena; Lyakhovetskii, Vsevolod; Kovalev, Gleb; Shkorbatova, Polina; Islamova, Regina; Pavlova, Natalia; Gorskii, Oleg; Merkulyeva, Natalia; Shkarupa, Dmitry; Musienko, Pavel (Frontiers in Systems Neuroscience, 2020)
Impairments of the lower urinary tract function including urine storage and voiding are widely spread among patients with spinal cord injuries. The management of such patients includes bladder catheterization, surgical and pharmacological approaches, which reduce the morbidity from urinary tract-related complications. However, to date there is no effective treatment of neurogenic bladder and restoration of urinary function. In the present study we examined neuromodulation of detrusor and external urethral sphincter by epidural electrical stimulation of lumbar and sacral regions of the spinal cord in chronic rats. To our knowledge it is the first chronic study where detrusor and external urethral sphincter signals were recorded simultaneously to monitor their neuromodulation by site-specific spinal cord stimulation. The data obtained demonstrate that activation of detrusor muscle mainly occurs during the stimulation of the upper lumbar (L1) and lower lumbar (L5-L6) spinal segments whereas external urethral sphincter was activated predominantly by sacral stimulation. These findings can be used for development of neurorehabilitation strategies based on spinal cord epidural stimulation for autonomic functions recovery after severe spinal cord injury.